1994
DOI: 10.1007/bf02015456
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of malposition of the liver and spleen: CT, MRI, nuclear scan and fluoroscopic imaging

Abstract: Thirteen children initially suspected to have an intrathoracic or intraabdominal mass had malposition of the liver and/or spleen discovered by ultrasound. This group consisted of five children with diaphragmatic eventration or hernia and eight with wandering spleen or liver. Careful ultrasonographic examinations were diagnostic in all patients; seven had surgical confirmation. CT, MRI, nuclear scan and fluoroscopic imaging were useful in select instances. The liver and spleen have a characteristic anatomic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…In cases of torsion associated with infarction, the spleen's attenuation has been reported to be considerably lower than that of the liver [1,2,8,10] and the differential diagnosis includes mesenteric or omental cysts and abscesses [2]. Low attenuation of splenic parenchyma was not observed on the pre-contrast CT scans in our patients, except for case 1.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In cases of torsion associated with infarction, the spleen's attenuation has been reported to be considerably lower than that of the liver [1,2,8,10] and the differential diagnosis includes mesenteric or omental cysts and abscesses [2]. Low attenuation of splenic parenchyma was not observed on the pre-contrast CT scans in our patients, except for case 1.…”
Section: Discussioncontrasting
confidence: 66%
“…Mild enhancement may be attributed to collateral circulation through the short gastric and left gastric veins [1] and/or the short gastric and pancreatic arteries [9]. It has been reported that splenic perfusion and viability of the spleen can also be assessed by Doppler ultrasonography [7,9] and scintigraphy [10,11]. Information concerning splenic perfusion is important for the surgeon, especially in younger children where splenopexy instead of splenectomy is the treatment of choice [2,5,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plain radiographs are usually nonspecific, but with marked splenic displacement, the splenic silhouette disappears, and gas-filled bowel loops may be noted in the splenic fossa. Barium enemas, scintigraphy, and angiography have been helpful in some cases in the past 3…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse increased echogenicity of the spleen may correspond to areas of hemorrhagic congestion at the time of surgery. 5 Use of color and duplex Doppler sonography allows evaluation of blood flow in the splenic parenchyma and in the major splenic vessels. 2,6 It has been reported that the absence of sonographically detectable flow in the splenic parenchyma may be due to insufficient sensitivity of color and duplex Doppler sonography to slow or low-amplitude blood flow.…”
Section: Discussionmentioning
confidence: 99%